2014
DOI: 10.1504/ijlt.2014.065752
|View full text |Cite
|
Sign up to set email alerts
|

Example-based feedback provision using structured solution spaces

Abstract: Intelligent tutoring systems (ITSs) typically rely on a formalised model of the underlying domain knowledge in order to provide feedback to learners adaptively to their needs. This approach implies two general drawbacks: the formalisation of a domain-specific model usually requires a huge effort, and in some domains it is not possible at all. In this paper, we propose feedback provision strategies in absence of a formalised domain model, motivated by example-based learning approaches. We demonstrate the feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…However, researchers have reported 100 -1,000 hours of authoring time for one hour of instructions in ITSs [3]; in addition, ITSs usually require an underlying domain theory such that their applicability is limited in areas where problems and their solution strategies are not easy to formalize [4,5]. In such domains, data-driven approaches are possible, providing feedback based on a set of existing examples for (correct) solutions of the underlying task [5,6]: If the students requires a hint on how to change her attempt to get closer to a correct solution, it can be compared to a similar example from the set, and the dissimilarities between her attempt and the example can be contrasted or highlighted in order to help the student to improve her own solution [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have reported 100 -1,000 hours of authoring time for one hour of instructions in ITSs [3]; in addition, ITSs usually require an underlying domain theory such that their applicability is limited in areas where problems and their solution strategies are not easy to formalize [4,5]. In such domains, data-driven approaches are possible, providing feedback based on a set of existing examples for (correct) solutions of the underlying task [5,6]: If the students requires a hint on how to change her attempt to get closer to a correct solution, it can be compared to a similar example from the set, and the dissimilarities between her attempt and the example can be contrasted or highlighted in order to help the student to improve her own solution [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…1). The results show a positive impact of the instruction that was positively rated by the learners [10], and the study also confirmed that manual feedback generation indeed means a lot of work, and that the ITS feedback methods have been assessed as potentially helpful in most cases [7]. Finally, we conducted a field study in an introductory programming course for Java programming, comparing the appropriateness of different exemplar selection strategies (user or sample solutions, full or partial solutions) for feedback provision.…”
Section: Advances and Resultsmentioning
confidence: 82%
“…A subset of the data set was manually coded in terms of quality for the purpose of later comparison with automated assessments. Also, we defined the term "solution space" in more detail, including both a technical dimension on how to analyze such spaces of learner (and sample) solutions using machine learning techniques, and a pedagogical dimension on how to give useful feedback to a learner's solution within such a space [10]. In addition, we identified several evaluation methods (e.g., pre-/post-testing) and criteria (e.g., learner's action after and before next instruction) that are suitable for measuring the impact of FIT ITS methods on human learning.…”
Section: Advances and Resultsmentioning
confidence: 99%
See 2 more Smart Citations